A community of interpretation: the use of 1 Corinthians 2.6-16 by Early Christians - Strawbridge, J (Peeters Publishers, 2013)
While ancient historians create and study surveys of extant literature to determine what texts form the core of Graeco-Roman literate education, biblical scholars have not used this approach to examine what scriptural texts might make up the core of early Christian teaching and formation. Based on a comprehensive survey of the Pauline epistles referenced in early Christian texts up to the time of Constantine, this paper aims to begin to remedy deficiencies in questions about early Christian teaching and formation. In particular, I will focus on one of the passages most used by early Christians in their writings: 1 Corinthians 2.6-16. What can the widespread and frequent use of this passage by early Christians tell us about the texts they knew and how they were using the Pauline epistles? By examining the many contexts in which this Corinthian passage is used, this paper concentrates on a selection of patristic texts in order to determine whether a community of interpretation or a diversity of use exists among patristic authors who rely on 1 Corinthians 2 within their writings. I have found, and as this paper attempts to illustrate, that early Christian writers use excerpts from this Corinthian passage in at least four distinct and yet connected ways: for rhetorical argument, for apologetic discourse, for exegesis of difficult texts, and for discussing wisdom and Christian formation. Looking at each of these uses in patristic literature throughout our time period, therefore, this paper not only demonstrates that a community of interpretation exists in how early Christians rely on 1 Corinthians 2.6-16, but also provides a foundation for further study of early Christian formation within the context of a Patristic reception of the Pauline epistles.